Rip your own digitizing your records and tapes - Kim, Casey (Course Technology, 2011)
Book Description: If you?re like many music lovers, you still have a lot of your music collection on old records and tape cassettes. You probably want to be able to listen to a lot of that music on your iPod, but re-purchasing all of it in digital form would cost you hundreds, if not thousands of dollars. Have no fear, this book provides an easy-to-read, non-technical guide to digitizing all of those records on the cheap. You?ll get an overview of the tools available to help you with the task and how to find them. From there, you?ll get a gentle introduction to the world of digital audio that focuses on the task at hand with no unnecessary tech-speak. You?ll also learn how to use the software that can digitize that music into your computer, including how to clean up tape hiss, hum, pops, and clicks from the material. You?ll even get tips on how to organize your MP3s and which MP3 players are the best buy. By the end of the book, you?ll have learned to transfer all of your old records and tapes to MP3s you can listen to on the go, remastered some of your scratched records and worn-out tapes, and learned a little bit of pro audio to boot. So what are you waiting for? Your new digital music library awaits you.